(untitled) (Research, Society and Development, 2020)
The aim of this study was to characterize the development of flowers and fruits in native species of the family Myrtaceae based on the BBCH scale in search for unique and unpublished information about the Brazilian flora. The study was conducted in the Native Fruit Collection of the Federal Technological University of Parana, Campus Dois Vizinhos. We carried out photographic monitoring of eight species of the family Myrtaceae: pitanga tree, araçá-amarelo tree, cereja-da-mata tree, jabuticaba tree, ubajaí tree, guabiju tree, guabiroba tree, and sete-capote tree. The phenological stages follow the general BBCH scale for fruit species, in which the complete cycle of plant development is subdivided into 10 main phases. This study is the first to describe the phenological stages of these species according to the BBCH scale, which facilitates verification of all phases of different vegetative and reproductive stages of the investigated species. Such scales may serve as important and useful tools for appropriate management of orchards, and thereby improved fruit cultivation.